Manual de procedimentos do Programa Subsídio Social Básico (PSSB) - INAS - Instituto Nacional de Acção Social (2022)
O presente Manual de Procedimentos (MdP) apresenta a definição do Programa Subsídio Social Básico (PSSB), os objectivos, as componentes, os grupos-alvo, os critérios de elegibilidade, os tipos de benefícios, os mecanismos e frequência de pagamentos, a permanência de beneficiários no programa e formas de saída, a transferência de beneficiários entre componentes do programa, bem como o seu ciclo operacional. Para além dos Guiões práticos que oferecem descrições detalhadas de cada processo a ser desenvolvido por todos os actores da implementação do PSSB, o Manual tem como objectivo orientar aos intervenientes e uniformizar os procedimentos a adoptar na implementação do PSSB.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental

Anuário Estatístico - Statistical Yearbook 2021 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2022)
As in previous editions, the Statistical Yearbook 2021 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2017-2021 series. The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia